HUBUNGAN ANTARA CITRA TUBUH DENGAN TINGKAT KEPERCAYAAN DIRI REMAJA PUTRI DI MADRASAH TSANAWIYAH (MTS) MUHAMMADIYAH 01 CIPUTAT KOTA TANGERANG SELATAN TAHUN 2024 - Laetitia Ayesha Camil; Saraswati, Dewa Ayu Sri; Wenny Sitanggang, Tantri (STIKes IMC Bintaro, 2024)
Introduction: Adolescent girls are an age group that is vulnerable to various problems, one of which is body image. Body image is a person's perception of their physical appearance. A positive body image can increase self-confidence, while a negative body image can decrease self-confidence.. Research Objective: to know the relationship between body image and the level of self-confidence of adolescent girls at MTS Muhammadiyah 01 Ciputat, South Tangerang City. Methods: Quantitative research design with a Cross Sectional approach. The sample technique used by researchers is the Quota Sampling technique with a total of 60 respondents. The research instrument was a questionnaire sheet. Analysis of research data using the Chi Squere test Research. Results: The results of the analysis of the relationship between body image and the level of self-confidence obtained that there are 34 (56.7%) students who have a good body image with good self-confidence. Conclusion: There is a relationship between body image and the level of self-confidence of adolescent girls of MTS Muhammadiyah 01 Ciputat, South Tangerang City (p-value 0.004; OR .5.3). Suggestion: Respondents are expected to accept and appreciate their bodies as they are. Keywords : Body Image, Confidence Level, Students.